“You’re never going to get a second chance if someone doesn’t give you a second chance” perspectives and experiences of landlords and advocates on implementing HOME among youth experiencing homelessness - Rose, Dominique M.; Yang, Jingzhen; Chavez, Laura; Jones, Leslie; Schneider, Jennifer H.; Ding, Kele; Boch, Samantha; Yilmazer, Tansel; Slesnick, Natasha; Kelleher, Kelly (Frontiers in Public Health, 2025)
IntroductionYouth experiencing homelessness (YEH), particularly those with prior legal system involvement, face significant barriers to securing stable housing, including stigma, limited income, and criminal background screenings. While supportive housing programs have improved outcomes for adults, few programs have been evaluated for youth. The Housing, Opportunities, Motivation and Engagement (HOME) trial is the first randomized controlled trial to evaluate a six-month supportive housing intervention for YEH using private-market rental assistance. This qualitative sub-study explored landlord and supportive housing advocate perspectives and experiences with implementing HOME for YEH including those with legal system involvement.MethodsWe conducted semi-structured video interviews with 12 participants: 8 landlords (4 HOME participants, 4 non-participants) and 4 housing advocates. Participants were either directly involved in HOME or had prior experience with supportive housing for YEH. Interview guides were informed by the Consolidated Framework for Implementation Research (CFIR) and piloted before being finalized. Interviews were transcribed verbatim and analyzed using template analysis, guided by CFIR’s five domains. Three researchers independently double coded each transcript, met regularly to resolve discrepancies, and refined codes through focused coding. ATLAS.ti software supported data analysis.ResultsFive themes emerged: (1) Program Features and Benefits, including guaranteed rent and youth stabilization; (2) Landlord and Advocate Profiles, highlighting landlord motivations, rental practices, and experience with youth facing homelessness and legal system involvement; (3) Internal System Factors, such as financial incentives and the pivotal role of advocates in bridging communication; (4) External Influences, including rental market constraints and stigma; and (5) Program Enhancement Strategies, with suggestions for longer-term leases, clearer communication, and expanded support resources.ConclusionImplementation of supportive housing for YEH with legal system involvement is shaped by financial, relational, and place-based factors. While guaranteed rent and advocate support facilitated landlord participation, stigma, rigid lease structures, and short program duration posed persistent barriers. Findings highlight the need for tailored, multi-level strategies that address structural inequities and promote long-term housing stability.